Le Magnus Liber Organi de Notre-Dame de Paris - Roesner, Edward H.; Everist, Mark; Léonin fl. 12th century (Monaco Éditions de l'Oiseau-Lyre, 1993)
MAGNUS LIBER ORGANIParisian Liturgical Polyphony from the 12th and 13th Centuries7 volumesGeneral Editor: Edward H. RoesnerThe Magnus Liber Organi was composed for the cathedral of Notre Dame, Paris, during the brilliant cultural Renaissance of the twelfth century and the first decades of the thirteenth century. The work of Leoninus and other musicians, it may be considered as the greatest single achievement in the development of early polyphony. The revision and renotation of the Great Book by Perotinus and his contemporaries were equally important; the creation of the three- and four-voice organa (the earliest known examples of music for more than two voices) is one of the most extraordinary moments in the development of Western polyphony. This new edition, undertaken by an international team of scholars working under Professor Edward H. Roesner, will present the Parisian liber organi in all its richness and diversity for the first time in a complete modern edition. Subscription to the series is open to individuals as well as institutions; each volume is also available separately.
Keywords: Notre-Dame de Paris (France); Middle Ages (500-1400); Vocal music; Religion; Organum; Catholicism